DESIGN, DEVELOPMENT AND EVALUATION OF FENOFIBRATE AND ROSUVASTATIN NANODROPLETS - Raman Suresh Kumar (European Scientific Journal, ESJ, 2014)
Fibrate and statin combinational therapy is used to treat severe and refractory mixed hyperlipidemia. Hence lipid based SNEDDS were prepared using the concentration oil (2:1) and SCoS (1:1) which resulted in enhanced extent of absorption and relative bioavailability of 1.69 (fibrate) and 1.64 (statin). An approximately 40% of drug was available for systemic circulation via lymphatic route of absorption. The results showed a significant difference between the marketed and the SNEDDS